Kajian atas Wacana Tasawuf dan Keutuhan Sosial Ernest Gellner - Riyadi, Abdul Kadir (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
This article seeks to scrutinize the thought of Ernest Gellner particularly his idea of tasawuf and its relation to social cohesion. He has raised a number of questions concerning the relation of Islam and tasawuf with modernity, which attract the attention of other scholars in the field. By modernity he means secularism, industrialism and national-ism. Motivated by secular and orientalist ideals, Gellner seems to have no ground in the ?normative? aspect of Islam. This study finds that he is equally not consistent. In the first instance, he tends to argue that Islam must be excluded from modernity because it is not in conformity with it. Then he speaks of what he calls higher Islam and lower Islam, the former being in line with modernity while the latter is not. With regard to this distinction, he urges that Muslim society undergoes what he calls a ?transition? from the lower to the higher Islam if it is to join the modern society and be part of the ?cohesive world?. The lower Islam should be left out because it teaches magic and encourages poverty. By bringing up this distinction, and not sticking to the consistent paradigm, Gellner?s thought on Islam and tasawuf vis-à-vis modernity is?it may be judged?dichotomous and even perplexed.